«ЖӘҲАНША» ДӘСТАНЫНЫҢ ӨЗИНЕ ТӘН ӨЗГЕШЕЛИКЛЕРИ - Мамбетов, Ж.Қ. (FAN va JAMIYAT, 2019)
The article is devoted to the study of ideas, educational peculiarities and problems in the edition of the Karakalpak folk epos «Jakhansha» in the interpretation of Kurbanbay-jirau. The author of the work analises the peculiarities of creation of heroes’ images in the plot of the epos, structure of the plot and compositional aspects. By the comparative method there were analysed positive and negative heroes with unnatural personages in the epos. In conclusion the author shows the author’s individual peculiarities in the creation of the epos.